Perancangan dan Pengujian Sistem Pengendali Sudut untuk Motor DC Brushless Menggunakan Kendali Algoritma P-D - Rizqi Andry Ardiansyah (Universitas Syiah Kuala, 2017)
Many industrial applications use servo motor because of its accuracy and user-friendly, but by using it in an application, a higher cost is required. To make an actuator with good precision and universal purpose but with lower cost, a position control system for brushless dc motor was built. To achieve a better precision in the position control for brushless DC motor, the system is utilized with a microcontroller ATmega 2560, an absolute encoder as a position sensor, and also Proportional-Derivative closed-loop control algorithm. In the final test, we obtained that the system worked well on average angular speed about 3.88º/ms and angle tolerance about 1º.